Nutritional status assessment of elderly using MNA tool in rural Belagavi: a cross sectional study - Patil, D. J.; Shindhe, M. M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Worldwide the elderly population gradually increasing and that will definitely pose several challenges. Malnutrition is one of the major but neglected problem in elderly. They are at risk of malnutrition due to physical, psychological, social, dietary and environmental risk factors. Malnutrition in elderly is associated with adverse health effects. Hence to study the nutritional status of elderly. Methods: The study was carried out between January 2016- June 2017. 545 elderly were included in the study. Out of the 6 subcentres, 1 subcentre (Uchagaon) was selected by simple random sampling technique and house to house survey was carried out to select eligible elderly participants in the villages of selected subcentre. Data was collected from eligible elderly by using mini nutritional assessment (MNA) tool. Results: Majority of the participants (65.1%) were between the age group of 60-69 years. 55% were females. 23.5% were malnourished, 49% were at risk of malnutrition and 27.5% had normal nutritional status. Conclusions: The present study concluded that majority of the elderly were at risk of malnutrition. There is a need of actions to improve the nutritional status of the elderly.